Estimation of Maximal Work Rate Based on the 6-Minute Walk Test and Fat-Free Mass in Chronic Obstructive Pulmonary Disease - Cavalheri, Vinicius [UNESP]; Hernandes, Nidia Aparecida [UNESP]; Camillo, Carlos Augusto [UNESP]; Probst, Vanessa Suziane; Ramos, Dionei [UNESP]; Pitta, Fabio [UNESP] (W B Saunders Co-elsevier Inc, 2010)
Cavalheri V, Hernandes NA, Camillo CA, Probst VS, Ramos D, Pitta F. Estimation of maximal work rate based on the 6-minute walk test and fat-free mass in chronic obstructive pulmonary disease. Arch Phys Med Rehabil 2010; 91:1626-8.Objective: To propose a predictive equation of the maximal work rate (Wmax) in patients with chronic obstructive pulmonary disease (COPD) based on the product of 6-minute walking test (6MWT) and fat-free mass (FFM) and to compare it with a previously proposed equation based on the product of 6MWT and body weight (BW).Design: Descriptive (cross-sectional) study.Setting: University-based rehabilitation center.Participants: Patients with COPD (N=53; 30 men; forced expiratory volume in I second, 45%+/- 15% predicted).Interventions: Not applicable.Main Outcome Measures: Three Wmax were produced: Wmax_real (obtained from the maximal cycle ergometry test), Wmax_BW (estimated from the product of 6MWT and BW), previously proposed by Hill et al. (Arch Phys Med Rehabil 2008; 89(9):1782-7); and Wmax_FFM (estimated from the product of 6MWT and FFM).Results: The equation derived from a regression model to estimate Wmax_FFM was as follows: -27.9717+ 3.7792*(6MWT*FFM). Wmax_real correlated better with Wmax_FFM (r=.64) than with Wmax_BW (r=.54). There was no difference between Wmax_FFM (median [interquartile range], 41 [29-50] W) and Wmax_real (40 [20-50] W, P=.88), whereas Wmax_BW (60 [52-69] W) significantly overestimated Wmax_real (P<.0001).Conclusions: In patients with COPD, Wmax is better estimated by an equation including the product of 6MWT and FFM than by a previously proposed equation including the product of 6MWT and body weight.
Keywords: Pulmonary disease; chronic obstructive; Rehabilitation